Gender Differences in Eating Behavior - Lin, Khor Geok; Cobiac, Lynne; Skrzypiec, Grace (Nutrition Society of Malaysia, 2002)
University students may encounter personal, family, social, and financial stresses while trying to cope with their academic challenges. Such constraints could affect their eating behavior and health status which, in turn may have negative effects on their studies. In light of little information in Malaysia on this subject, this study was undertaken on a sample of 180 students pursuing different academic programs in a Malaysian university. The study objectives were to determine the students’ eating behavior including body weight control and the extent of fear of being fat, their social self concept that reflects the five selves namely, the psychological self, the social self, the sexual self, the family self and the physical self. Eating behavior and social self concept were determined based on various methods previously validated in studies on young adults in Asia and Australia. This article focuses on gender comparisons for these determinants. The results showed that psychological and emotional factors have a significant bearing on the eating behavior of university students. Uninhibited eating behavior of both the males and females showed significant and negative correlations with feelings pertaining to personal worth, the physical self, and their relationships with peers and families. Gender differences were manifested for some determinants. The females showed more restrained eating behavior than the males; the females have a significantly higher score for family relationship, which appears to be a significant factor on male students’ eating behavior. Future studies on a larger sample size may help to unravel the extent to which psychological factors influence eating behavior of students, and the underlying psychosocial basis for some of the gender differences reported in this study.